Effect of ESAT-6 on Phagocytosis Activity, ROS, NO, IFN-γ, and IL-10 in Peripheral Blood Mononuclear Cells of Pulmonary Tuberculosis Patients - Dicky Santosa; Dida Akhmad Gurnida; Herri S. Sastramihardja; Anas Subarnas (Global Medical & Health Communication (GMHC), 2022)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (MTB) that lives intracellularly. MTB can inhibit lysosomal enzymes and phagolysosomal fusion, which is challenging to eliminate. These are due to ESAT-6/CFP-10 originating from the RD1 region genome that expresses the Esx-1 type VII secretion system. Esx-1 encodes Esx-A (ESAT-6) and Esx-B (CFP-10), potential vaccine candidates still under research and development. ESAT-6/CFP-10 is predicted to affect macrophage phagocytic activity, IFN-γ, ROS/NO, and IL-10 levels. Several studies have begun to focus on the ESAT-6 antigen due to the high levels of ESAT-6 antibody found in pleural effusion and granuloma fluid. They can last up to 1 year compared to CFP-10 in experimental animals. This study aimed to analyze the effect of ESAT-6 on the phagocytic activity of macrophages, ROS/NO, IFN-γ, and IL-10 in peripheral blood mononuclear cells (PBMCs) cultures of pulmonary TB patients. It is experimental laboratory research with a post-test-only control group design with PBMCs from October 2019 to December 2020 in the Aretha Laboratory Bandung. There were two groups: the negative group (without ESAT-6) and the positive group (with ESAT-6). Six subjects were sampled at the Pindad Hospital in Bandung, and the research was carried out at the Aretha Laboratory in Bandung. Statistical analysis using paired t test. There was a significant difference between the negative and positive groups (p<0.05). ESAT-6 can decrease macrophage phagocytic activity, intracellular ROS/NO, and IFN-γ but increase IL-10 levels.